The principles of Good Living in the relationship with women's protagonism (Research, Society and Development, 2022)
This article seeks to discuss, from a theoretical-practical perspective, the principles of Good Living in relation to the protagonism of women from the Arruda quilombo. We do so, with an interest in reflecting on the Social Movement of Quilombola Women in the community of Arrudas - CE, in light of the precepts of Good Living. The option is to focus on the political dimension of their claims and proposals, seeking to make the analysis contribute to reflecting on public policies in their own terms. Furthermore, the collective action and its self-attribution as quilombola women are analyzed, taking into account possible connections and disconnections with other feminisms, in order to trace the logic of politics in face of the valorization of the role of women. This analysis allows us to glimpse how quilombola women move between these two logics of action, but it also encourages scheduling discussions that are anthropologically related to the relationship between ontology and politics. To account for this research interest, we adopted a literature review with qualitative contributions as a methodology. Finally, we can affirm the relationship between the women's social movement and the precepts of Bem Viver.